Zygomycosis in a renal allograft recipient - Lakshminarayana, G. (Medknow Publications, 2009)
Invasive fungal infections can cause considerable morbidity and mortality in immunocompromised patients. Zygomycosis is a type of invasive fungal infection with a rapid course and grave prognosis. Renal transplant recipients with concomitant diabetes mellitus are most susceptible to this infection. We report here a case of disseminated zygomycosis (Rhizopus sp.) in a renal allograft recipient with posttransplant diabetes mellitus (PTDM). This is the first reported case of zygomycosis caused by Rhizopus species.